Effectiveness of Motivational Self Talk on Self-Confidence in Athletes at Football Schools - Alzamora, Davano Arta; Mufidah, Annisa’ Al; Artanti, Dewi Sri Lestari Putri; Ramadani, Dian Novita; Hamidah, Dwi Andini Nurul; Abrorry, Lucky (International Conference on Sustainable Health Promotion, 2023)
This study aims to determine the effectiveness of motivational self-talk on increasing athlete’s selfconfidence. The research method is experimental with a one group pretest-posttest type design. The population taken was SSB New Star Salam athletes, totaling 20 children aged 9-10 years. The analysis uses the Wiloxon test statistic. This research produces evidence that the technique of motivational self-talk through a sports approach is proven to be effective in increasing the confidence of soccer athletes. This is based on a Z value of -3,922 with a p value of 0.000 (p <0.05) which indicates a significant difference in the level of athlete’s confidence between before and after the motivational self-talk intervention.